Students’ attitude to virtual teaching of the english language in secondary schools in oyo state: implications for students achievement - Olatunji, Sheriff Olamide (ARKA INSTITUTE, 2022)
This study investigated students’ attitude to virtual teaching of English Language: Implications for students’ achievement. The study adopted the survey research design. Three private secondary schools were randomly selected from private secondary schools in Ibadan North Local Government Area, Oyo State. From each school, 50 SSII students were randomly selected making a total of 150 students. One research instrument was used for data collection: Questionnaire on Students’ Attitude to Virtual Teaching (r=0.82). Data collected were analysed using descriptive statistics of percentage, mean, standard deviation and inferential statistics of t-test. Findings of the study revealed the weighted mean of 2.499 out of the 4.00 maximum obtainable scores, which is higher than the standard mean of 2.50. This means that students had a good attitude to virtual teaching. There was no significant difference between male and female students’ attitude to virtual teaching (t = -.414; df=148; p>0.05). Based on the findings of this study, it was recommended that students should be encouraged to have positive attitude to virtual teaching of English Language. Teachers and students should be trained on how to use different virtual platforms for teaching and learning of English Language.